Knowledge of fermentation and health benefits among general population in North-eastern Slovenia - Maja Šikić-Pogačar; Dušanka Mičetić Turk; Sabina Fijan (BMC, 2022)
Abstract Background Fermented foods are staples of the human diet and fermentation process has been used by humans for thousands of years. The preparation of fermented foods was performed in the past without knowledge of the role of microorganisms involved. Nowadays, fermented foods, due to their proclaimed health benefits for consumers, are becoming increasingly popular. Our study was constructed to provide data on awareness and use of fermented foods among people in North-eastern Slovenia. Methods The cross-sectional study included 349 individuals (16-89 years of age). An online survey was designed to assess the participants' knowledge of fermentation, fermented foods, the consumption of fermented foods and awareness of the health benefits. Data were collected from March to June 2021 and analyzed using IBM SPSS 27.0. Results Compared with the youngest participants (< 21 years) knowledge of fermentation was higher in older individuals (p < 0.001). More than a half of the participants recognized the role of lactic acid bacteria and yeasts in fermentation process, however, only 18.3% of participants were aware of the role of the molds. Only 25.9% of the participants have become acquainted with fermented foods at home and 62.2% of them were aware of health benefits of fermented foods, but mostly on gastrointestinal health and the immune system. Conclusions As people today live predominantly in urban areas and incline towards westernized foods, they often lack the knowledge of fermentation and awareness regarding the nutritional value of fermented foods and their preparation. Steps should be taken to educate younger generations regarding the health benefits of fermented foods especially considering that most of them expressed their interest in learning more about the process.